Utility and the Pleasures of Musical Formalism: Edmund Gurney, Liberal Individualism, and Musical Beauty as 'Ultimate' Value. Issue 2 (20th August 2019) - Collins, Sarah
Abstract: Most contemporary assessments of Edmund Gurney's musical thinking rely solely on his influential book The Power of Sound (1880), yet much of the work that appeared in this book was initially published in essay form in the liberal press, appearing alongside discussions of politics, economics, moral philosophy, and psychology. With this broader frame in mind, this article investigates the relationship between Gurney's musical thinking and the traditions of utilitarianism, political economy, and liberalism through his association with Henry Sidgwick's circle. It argues that one of the central tenets of Gurney's musical formalism—namely the idea that there is an irreducibly 'musical' form of beauty—may be construed in relation to 'liberal individualism' as it was framed by the utilitarian liberals with whom he associated, who attempted to combine the cultivation of disinterestedness with the pursuit of pleasure as a means to attaining a balance between self-interest and the common good.